Determinants of Chronic Energy Deficiency in Pregnancy at Lebak Wangi Community Health Center, Banten, Indonesia - Rahmadhena, Melisa Putri; Astuti, Erlin Wibi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2026)
Background: Malnutrition during pregnancy increases the risk of anemia, hypertension, miscarriage, fetal death, and causes low birthweight and fetal growth disorders that have a long-term impact on quality of life and health costs. Understanding and analyzing the problem of chronic energy deficiency in pregnant women based on comprehensive determinants is indispensable in order to design appropriate policies and treatment actions. This study aims to analyze the influence of the determinants of the incidence of chronic energy deficiency in pregnant women.Subjects and Method: This is a case control study conducted at the